Efficacy and safety of a “radical” surgical strategy in the treatment of parasagittal sinus meningioma - Duan, Zihao; Zhou, Changlong; Yan, Xiaoxiao; Du, Wei; Xia, Xiaohui; Shi, Hui; Su, Hai; Zhang, Yi; He, Xuenong; Xiong, Qijiang (Frontiers in Neurology, 2024)
Background No standardized criteria for surgical resection of parasagittal sinus meningiomas (PSM) have been established, and different surgical strategies have been proposed. The aim of the present study was to investigate the efficacy and safety of a “radical” surgical strategy in the treatment of PSM. Methods The clinical histories, radiological findings, pathologic features, and surgical records of 53 patients with PSM admitted by the same surgical team using the “radical” surgical strategy were retrospectively analyzed between 2018 and 2023. Results Among the 53 PSM cases, 16 (30.2%) had a patent sinus proper, 28 (52.8%) had partial obstruction of the sinus proper, and 9 (17.0%) had complete obstruction of the sinus proper before the operation. During operation, Simpson grade I resection was performed in 34 (64.2%) cases and Simpson grade II in 19 (35.8%) cases. Postoperative pathologic examination suggested tumors of WHO grade I in 47 (88.7%) cases, WHO grade II in 4 (7.5%) cases, and WHO grade III in 2 (3.8%) cases. Postoperative complications primarily included a small amount of delayed intracerebral hemorrhage in 3 (5.7%) cases, exacerbation of cerebral edema in 3 (5.7%) cases, exacerbation of motor and sensory deficits in 4 (7.5%) cases, and intracranial infection in 2 (3.8%) cases. There were no cases of death or new-onset neurological dysfunction. Dizziness and headache symptoms improved to varying degrees, and a seizure-free status was achieved postoperatively. Excluding one case lost to follow-up, the average follow-up period was 33 months, and there were no cases of recurrence. Conclusion A “radical” strategy for the surgical management of PSM is effective, safe, and simple to perform, provided that the sagittal sinus is properly managed and its associated veins are protected.